A basis for comparing progressive collapse resistance of moment frames and connections. (December 2017) - Li, Ling; Wang, Wei; Chen, Yiyi; Teh, Lip H.
Abstract: The progressive collapse resistance of a moment frame in the event of an inner column loss has been studied in terms of either the beam span or the beam span-to-depth ratio. This study reiterates that, strictly speaking, it is the beam span-to-depth ratio that is the underlying factor. Basically the larger the span-to-depth ratio, the better the progressive collapse resistance if the beams have been similarly optimised against plastic hinging under the design floor load. In comparing the performance of various types of steel double-span assemblies against each other, it would not always be appropriate to normalize their resistance against the same uniformly distributed load on the floors unless the beams have been similarly optimised. This article explains how the progressive collapse resistance of various types of steel double-span assemblies can be clearly compared against each other with respect to their development of the catenary mechanism, independently of the optimisation extent of the beam section against plastic hinging under the design floor load. The quasi-static resistance is normalized against the plastic hinge load, and the chord rotation is normalized against the plastic rotation. The proposed procedure further enables a rigorous comparison between different types of steel moment connections since the effects of different beam sections and different spans are filtered out under the same span-to-depth ratio. Issues such as the dynamic effects of sudden column loss, the contributory effects of floor slabs and the second-order effects of topological changes are not relevant to the present study. Highlights: Presents a basis for comparing the progressive collapse resistance of moment frames Presents a procedure for assessing the ability to develop catenary mechanism Demonstrates the effect of span-to-depth ratio on progressive collapse resistance Span-to-depth ratio rather than beam span is proven to be the underlying factor. Various moment connections can be properly compared irrespective of beams.